PRESERVATION OF CHICKEN BREAST MEAT BY ROSEMARY (Rosmarinus officinalis L.) (Vietnam Journal of Agriculture and Environment, 2023)
The study aims to extend the shelf - life of chicken breast meat by different treatments, including: (i) rosemary extract 14%, 16%, and 18%; (ii) rosemary essential oil 3%, 5%, and 7%; (iii) edible coatings formula (sodium alginate combined with rosemary extract or rosemary essential oil). The study evaluated the effect of these treatments on the physicochemical parameters (pH, color, shear force, drip loss) and microbiological indicators (Escherichia coli and aerobic plate count) of chicken breast meat during the cooling storage. The results showed that the physicochemical parameters of chicken breast meat were not be effected by different treatments, these parameters were good maintained during cooling storage (4 ± 10C). However, the antibacterial activity of rosemary extract was less effective to the growth of microorganisms, otherwise the rosemary essential oil 5% exhibits impressive antibacterial properties, including the growth of E. coli and aerobic plate count during seven days of storage. Moreover, the chicken breast meat was treated with sodium alginate - rosemary essential oil 5% had the E. coli and the aerobic microbial plate count within Vietnamese national standards (TCVN 12429-3: 2021) during ten days of cooling storage.